Statistical and synoptic analyses of offshore wind variations. (10th February 2019) - Bakri, Talaat; Jackson, Peter
Abstract : In this study, variations of offshore wind speed in the northern and central coasts of British Columbia are examined using wind observations from nine buoys distributed in the region. Wind speeds from all buoys are extrapolated to the standard (10 m) wind measurement height as well as to the wind turbine hub height (100 m) using Monin–Obukhov similarity theory. Sustained winds above several thresholds are analysed and values of 50 and 100‐year return extreme wind speed levels are calculated for all locations. The percentage of sustained winds between the wind turbine cut‐in and cut‐out wind speed thresholds at 100 m indicates short periods without power generation. The highest 50 and 100‐year return level values are found at locations west of Haida Gwaii, while the lowest values are calculated at the most southern and eastern locations. Spatial coherency analysis of high wind speeds between all locations shows high same‐day coherency ratios between all buoys located offshore of the mainland coast, which emphasizes the importance of the atmospheric circulation at the synoptic‐scale as the main driver of intense wind events; consequently, a synoptic‐scale circulation analysis is carried out by applying principal components analysis and k ‐means clustering, and then relating the calculated synoptic patterns to some of the previously classified wind categories. The synoptic‐scale circulation analysis reveals that high wind speed events are mainly associated with a system of low pressure located west or northwest of the study region, which induces intense southerly to southeasterly winds. Low wind speeds are often associated with a high‐pressure system (Pacific High) originating southwest of the region that mainly predominates during the summer. Abstract : The intermittency of wind speed is the main uncertainty associated with the Wind power production; therefore identifying the mean duration and frequency of continuous periods of wind speed above and below particular thresholds is a key feature for wind resource assessments. In addition, understanding wind variability would certainly be improved by investigating spatial coherency of intense wind events. The results of this study emphasize the importance of wind variability analysis as a needed step for wind resource assessments.